EFISIENSI PENGOLAHAN LIMBAH OLI BENGKEL MENGGUNAKAN REAKTOR DISSOLVED AIR FLOTATION PADA SKALA LABORATORIUM - Muhammad Irfa'i (Purifikasi, 2007)
The increasing number of car service stations in Banjarmasin might increase the generation of hazardous oil waste to the environment. This research was aimed to -obtain the optimum efficiency of a laboratory scale Disolved Air Flotation (DAF) for reducing oil waste pollutant concentration. The reactor was designed based on some variations of detention time, air supply and feeding rate. The experiment was expected to result in optimum design criteria for reducing oil waste pollutant. This research was conducted on a laboratory scale DAF system. Result of this research showed average oil/grease removal efficiency of 86,65% for the detention time of 30 minutes, with by DAF system, mean 85,62% at giving of air 45 L/minutes and 89,94% for high feed (K3). Based on Two Way ANOVA test of significant difference of exclusion of oil waste which significant at variation giving of air, time contact and giving feed.